Analysis Mycobacterium lepromatosis as the causative agent of diffuse lepromatous leprosy patient in Indonesia - MEDHI DENISA ALINDA; ABDUL KARIM; BAGUS H. KUSUMA PUTRA; ERY WIDAYATI; M. YULIANTO LISTIAWAN; DINAR ADRIATY; ISWAHYUDI ISWAHYUDI; PUPUT ADE WAHYUNINGTYAS; CITA ROSITA PRAKOESWA (Society for Indonesian Biodiversity, 2023)
Abstract. Adriaty D, Alinda MD, Karim A, Putra BHK, Agusni RI, Iswahyudi, Wahyuningtyas PA, Wahyuni R, Widayati E, Listiawan MY, Prakoeswa CR. 2023. Analysis Mycobacterium lepromatosis as the causative agent of diffuse lepromatous leprosy patient in Indonesia. Biodiversitas 24: 4521-4529. The present investigation deals with identifying, besides clinical signs, both microscopically and molecularly, to clearly differentiate the Mycobacterium lepromatosis genome against Mycobacterium leprae so that treatment can be carried out properly. To date, there has yet to be a report on this discovery in Indonesia. A 53-year-old Javanese man had ulceration on both legs that had been reoccurring in the past two years. Some of the ulcers were preceded by blisters that rapidly turned into a wound. The ulcers were described as wide and deep, covered with blackish crusts and some exudative areas with irregular edges. He had a history of recurrent epistaxis and had never been treated for leprosy. There was rapid progression and the development of new ulcers on his legs and hands for two weeks before hospitalization. There was body weakness, no fever, and the skin was shiny and ichthyosiform. On the face, diffuse infiltration will appear without nodules, and madarosis also occurs. Examination in this study used the BTA examination method, histopathological examination with HE and Wade-fite staining with biopsy material and the PCR method using skin slit smear material. The results of the BTA examination showed that BI was 3+, and MI showed 7%. Histopathology showed thinning of the epidermis with many foam cells containing BTA, including endnotes and perivascular tissues. Nested PCR examination with LERF2-MLER4 primers for detecting M. leprae showed a positive result with amplicon 135bp in size. Advanced PCR examination using LPMF2-MLER4 primers for detecting M. lepromatosis also showed a positive result with amplicons 142bp in size. The result of DNA sequencing was consistent with the order of nucleotides of M. lepromatosis. Based on the clinical and histopathological results, it was consistent with diffuse lepromatous leprosy and Lucio’s phenomenon. The DNA sequencing showed a suitable result with M. lepromatosis, which has been reported in Mexico. Thus, it can be concluded that in biomolecular strain, this bacterium is an M. lepromatosis that has never been reported in Indonesia.